Near-Infrared Phosphorescence Emission of Binuclear Mn(II) Based Metal-Organic Framework for Efficient Photoelectric Conversion - Zhang, Mei-Li; Zhai, Zhi-Min; Yang, Xiao-Gang; Huang, Ya-Dan; Zheng, Yan-Jin; Ma, Lu-Fang (Frontiers in Chemistry, 2020)
The development of metal-organic framework (MOF) based room-temperature phosphorescence (RTP) materials has raised extensive concern owing to their widespread applications in the field of anti-counterfeiting, photovoltaics, photocatalytic reactions and bio-imaging. Herein, one new binuclear Mn(II) based 3D MOF [Mn2(L)(BMIB)•(H2O)] (1) (H5L = 3,5-bis(3,5-dicarboxylphenxoy) benzoic acid, BMIB = tran-4-bis(2-methylimidazolyl)butylene) has been synthesized by a facile hydrothermal process. In 1, the protonated BMIB cations show infinite π-stacking arrangement, residing in the channels of the 3D network extended by L ligand and binuclear Mn(II) units. The orderly and uniform host-guest system at molecular level emits intense white light fluorescence and long-lived near infrared phosphorescence under ambient condition. These photophysical process were well studied by density functional theory (DFT) calculations. Photoelectron measurements reveal high photoelectron responds behavior and incident photon-to-current efficiency (IPCE).